(untitled) (Comprehensive Journal of Science, 2025)
This study aims to evaluate the performance of faculty members from the perspective of students of technical higher education institutions in the city of Zuwara. In order to identify the level of teaching performance in three areas (personal relationships, teaching efficiency, and time management and organization of lectures) The descriptive analytical approach was used. And collect data By a questionnaire consisting of (21) paragraphs It was applied to a random sample of (76) male and female students. From (College of Engineering Technology, Higher Institute of Technical Sciences, and Higher Institute of Marine Sciences Technologies) The SPSS statistical analysis program was used to process and analyze the data. The results of the students’ evaluation of the faculty members’ performance were reached. It came at an average level in all fields, as the general arithmetic mean reached (3.63). The field of time management and lecture organization was at a high level, with an arithmetic mean of (3.69). Followed by the field of teaching efficiency at an average level, with an arithmetic mean of (3.65). While the field of personal relationships came in last place with an average level and an arithmetic mean of (3.54). The study also showed that there were no statistically significant differences in students’ responses depending on the gender variable. And also depending on the educational institution variable. While there are statistically significant differences in students’ responses depending on the variable of academic level. The study recommends the need to develop teaching skills and vocational training. Positive relationships with students, enhancing time management and organizing lectures This contributes to improving the quality of technical education and raising the efficiency of the outputs of technical education institutions.